Haptoglobin Polymorphism and Association with Complications in Ghanaian Type 2 Diabetic Patients. - Adinortey, M.B.; Gyan, B.A.; Adjimani, J.; Nyarko, P.E.; Sarpong, C.; Tsikata, F.Y.; Nyarko, A. (My University, 2011)
There is scanty information on the role of genetic factors, especially those relating to haptoglobin (Hp) phenotypes in the expression of complications among diabetes mellitus patients in Ghana. In this study, we investigated whether there is any association between Hp phenotypes and diabetic complications and to determine if association of the Hp phenotypes with diabetic complications in Ghanaian diabetics differ from those in Caucasians. A total of 398 participants were randomly recruited into the study. These comprised diabetic patients numbering 290 attending a diabetes Clinic in Ghana and 108 non-diabetic controls from the same community. Analyses of the results indicate that most of the diabetics with complications were of the Hp 2–2 (35%) and Hp 2–1 (23.9%) phenotypes. Fewer diabetics were found to be of the Hp 2–1 M phenotype. The controls were mostly of Hp 1–1 and Hp 2–1 M phenotypes. The odds ratio of having complications in a diabetic with an Hp 2–2 phenotype was 18.27 times greater than that for Hp 0–0. Hp 2–2 phenotype with its poor antioxidant activity may therefore be a useful predictor for the propensity of an individual to develop diabetes complications.
Keywords: Diabetes mellitus; Antioxidants; Haptoglobin phenotype